RESPON TERAPI ANTIRETROVIRAL PADA PASIEN HIV/AIDS DI RSUP DR. SARDJITO YOGYAKARTA - , DWI PUTRI SAFNURBAITI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The use of antiretroviral drugs (ARV) can suppress HIV viral replication, increasing the life expectancy of people with HIV/AIDS (PLWHA) and the quality of life of people living with HIV. Activity monitoring clinical response, immunological, and virulogis routinely required in patients with HIV / AIDS to monitor the success and failure of antiretroviral therapy. The study aimed to determine the response of antiretroviral therapy based on clinical and immunological markers in patients with HIV / AIDS in RSUP Dr. Sardjito. This is a cross sectional descriptive research and the data are collected retrospectively from the patient medical record. Descriptive statistic is used to analysed the data. The data are taken from the patient who meet the criteria, which is over 18 years old patient, own complete medical record, diagnosed early and/or advanced stage, own CD4 data and weight a minimum two data. The response therapy can be seen from immunological markers, which is changes in CD4 and clinical markers such as changes in body weight. Totality there are 63 HIV/AIDS patient which meet inclusion criteria. The result of research indicate in first line ARV therapy regimen that combination of zidovudin+lamivudin+nevirapine is used mostly exactly for 24 patients (38,10%). CD4 count increase after ARV therapy in 6, 12, dan 24 months are occur on 27 patients (81,82%), 40 patients (83,33%), and 43 patients (82,69%). Increasing of body weight in 6, 12, and 24 months after therapy ARV are 34 patients (72,34%), 33 patients (82,50%), and 36 patients (81,82%). Increasing of body weight not always followed increasing of CD4 count after six months ARV therapy